Business Plan - Scholar Warriors (confidential) - Aujla, Kamaljit (2013)
This is a business plan for a Martial arts academy which has been adapted to suit the needs of modern society and culture. The academy aims to increase customer value proposition by offering transport for children and teaching from a specially designed syllabus. In addition, childcare services will be offered in the form of an after school club, providing each child with transportation, a healthy meal and academic tuition. A competitive advantage will be achieved by combining these services, and saving the customer both time and money.